2022
DOI: 10.1021/acs.jpclett.2c01509
|View full text |Cite
|
Sign up to set email alerts
|

1D α-Fe2O3/ZnO Junction Arrays Modified by Bi as Photocathode: High Efficiency in Photoelectrochemical Reduction of CO2 to HCOOH

Abstract: Photoelectrocatalytic (PEC) CO2 reduction to value-added chemicals is a promising solution to address the energy and environmental issues we face currently. Herein, a unique photocathode Bi@ZFO NTs (Bi and α-Fe2O3 co-modified ZnO nanorod arrays) with high utilization of visible light and sharp-tips effect are successfully prepared using a facile method. Impressively, the performance of Bi@ZFO NTs for PEC CO2 reduction to HCOOH included small onset potential (−0.53 V vs RHE), Tafel slope (101.2 mV dec–1), and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…The stronger PL signal intensity represents the higher recombination rate of electron–hole pairs. 44,45 The peak intensity of bulk CN was stronger than that of CSCN-2, reflecting the inhibited recombination of photoexcited carriers after oxygen bridge modification, and is beneficial for photocatalytic CO 2 reduction (Fig. 8a).…”
Section: Resultsmentioning
confidence: 99%
“…The stronger PL signal intensity represents the higher recombination rate of electron–hole pairs. 44,45 The peak intensity of bulk CN was stronger than that of CSCN-2, reflecting the inhibited recombination of photoexcited carriers after oxygen bridge modification, and is beneficial for photocatalytic CO 2 reduction (Fig. 8a).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the more negative potential required for the production of CO might be due to the higher formation energy barrier of *COOH compared with that of *OCHO on Sn-based catalysts. 44 As the potential became more negative, the FE of CO displayed a volcano-like tendency. The peak values of 28.7% and 21.9% were observed at −0.76 and −0.86 V for SnO 2 /g-C 3 N 4 and SnO 2 /rGO, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This photocathode was reported to be stable for 24 h operation under 1 sun illumination at −0.2 V RHE with 86.5% CO selectivity and a comparatively high photocurrent density of 5.1 mA cm −2 . In 2022, Ouyang et al 139 reported a 1D rough-surface α-Fe 2 O 3 /ZnO heterostructure nanorod array with Bi modification showing formate selectivity. The authors claimed that the sharp tip benefits from an accumulation of electrons on the active site, which enhances the catalyst activity.…”
Section: Benchmarking Of the Materials And Processes For The Co2rrmentioning
confidence: 99%